ENIGMA‐Sleep: Challenges, opportunities, and the road map. (28th April 2021) - Tahmasian, Masoud; Aleman, André; Andreassen, Ole A.; Arab, Zahra; Baillet, Marion; Benedetti, Francesco; Bresser, Tom; Bright, Joanna; Chee, Michael W.L.; Chylinski, Daphne; Cheng, Wei; Deantoni, Michele; et al.
Summary: Neuroimaging and genetics studies have advanced our understanding of the neurobiology of sleep and its disorders. However, individual studies usually have limitations to identifying consistent and reproducible effects, including modest sample sizes, heterogeneous clinical characteristics and varied methodologies. These issues call for a large‐scale multi‐centre effort in sleep research, in order to increase the number of samples, and harmonize the methods of data collection, preprocessing and analysis using pre‐registered well‐established protocols. The Enhancing NeuroImaging Genetics through Meta‐Analysis (ENIGMA) consortium provides a powerful collaborative framework for combining datasets across individual sites. Recently, we have launched the ENIGMA‐Sleep working group with the collaboration of several institutes from 15 countries to perform large‐scale worldwide neuroimaging and genetics studies for better understanding the neurobiology of impaired sleep quality in population‐based healthy individuals, the neural consequences of sleep deprivation, pathophysiology of sleep disorders, as well as neural correlates of sleep disturbances across various neuropsychiatric disorders. In this introductory review, we describe the details of our currently available datasets and our ongoing projects in the ENIGMA‐Sleep group, and discuss both the potential challenges and opportunities of a collaborative initiative in sleep medicine.